Nanohardness of a Ti thin film and its interface deposited by an electron beam on a 304 SS substrate - Vieira, R. A.; Nono, M. C.A.; Cruz, N. C. [UNESP] (My University, 2002)
The results of nanohardness measurements at a film surface and film-substrate interface are presented and discussed. An electron beam device was used to deposit a Ti film on a 304 stainless steel (304 SS) substrate. The diluted interface was obtained by thermal activated atomic diffusion. The Ti film and Ti film-304 SS interface were analyzed by energy dispersive spectrometry and were observed using atomic force microscopy. The nanohardness of the Ti film-304 SS system was measured by a nanoindentation technique. The results showed the Ti film-304 SS interface had a higher hardness value than the Ti film and 304 SS substrate. The Ti film surface had a lower hardness due to the presence of a TiO2 thin layer.